Clinical and Functional Features of Acute Bronchitis in Infants on Connective Tissue Dysplasia - E. E. Krasnova; V. V. Chemodanov; A. A. Baldaev (Вопросы современной педиатрии)
The paper presents the features of acute bronchitis in infants, occurring against the background connective tissue dysplasia. Its modifying influence on the clinical and functional characteristics of disease, including recurrent course of acute bronchitis, is shown. Different types of bronchial obstruction are demonstrated. It is recommended to use the method of bronchophonografia to verify them in infants